Pressure-strain product reflects left ventricular stroke work under a wide range of left ventricular assist device support levels - Sato, Kei; Yoshida, Yuki; Yokota, Shohei; Matsushita, Hiroki; Morita, Hidetaka; Fukumitsu, Masafumi; Nishikawa, Takuya; Uemura, Kazunori; Kawada, Toru; Saku, Keita (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAssessment of native cardiac function is vital in patients with cardiogenic shock supported by a left ventricular assist device (LVAD), as it is directly related to the critical decision of LVAD management. Left ventricular stroke work (LVSW) can be useful for cardiac assessment to predict survival in cardiogenic shock patients; however, this measurement cannot necessarily be obtained under LVAD support, especially in cases where the aortic valve is closed (i.e., total support). Therefore, we propose a novel echocardiographic parameter named the pressure-strain product (PSP), the product of left ventricular (LV) pressure and LV myocardial strain, as this measurement can be calculated even under LV total support. This study aimed to investigate whether PSP was correlated with pressure-volume (PV) loop-based LVSW and myocardial oxygen consumption under LVAD support.MethodWe used 15 adult goats. An LVAD system was established during open chest surgery by draining blood from the left ventricle and returning it to the carotid artery. LV PV loops were analyzed by measuring LV pressure and volume using sonomicrometry. PV loop-based LVSW was defined as the area surrounded by PV loops. The PSP was defined as the product of the peak LV pressure and global circumferential strain (GCS) using speckle-tracking echocardiography. LVAD support levels were divided into three groups: control, and partial (with residual native cardiac output) and total (without native cardiac output) support. Myocardial oxygen consumption was measured using coronary flow and blood gas analyses. The correlation coefficient was measured using linear regression analysis.ResultsAccording to each LVAD support level at control, partial support, and total support, LVSW was 1,748 ± 867, 840 ± 467, and 290 ± 262 mmHg·ml, while PSP was 2,341 ± 507, 1,836 ± 768, and 539 ± 269 mmHg·%, respectively. PSP (r = 0.54) showed the strongest correlation with PV loop-based LVSW among other echocardiographic parameters, including LV end-diastolic volume (r = 0.37), GCS (r = 0.40), and echo-based LVSW (r = 0.50). PSP level was significantly associated with myocardial oxygen consumption (r = 0.55).ConclusionPSP significantly correlated with PV loop-based LVSW at various LVAD support levels. PSP can be a non-invasive parameter for assessing myocardial metabolism under LVAD support, potentially reflecting myocardial oxygen consumption.